110 Corneal biomechanical properties and vascular compliance in the UK biobank cohort. (May 2019) - Woodbridge, Simon; Kang, Swan; Aung, Nay; Biasiolli, Luca; Cooper, Jackie; Sanghvi, Mihir; Fung, Kenneth; Piechnik, Stefan; Neubauer, Stefan; Petersen, Steffen; Foster, Paul
Abstract : Introduction: Intra-ocular pressure (IOP) measurement is an integral part a comprehensive eye examination. In addition to IOP, corneal biomechanical characteristics such as corneal hysteresis (CH), a measurement of viscoelastic compliance, and corneal resistance factor (CRF), derived from corneal deformability, have also been identified as useful indicators of incidence and progression of primary open angle glaucoma (POAG) (1, 2). Corneal tissue shares compositionally similar properties with arterial tissue (3, 4). Our cross-sectional observational study aimed to ascertain whether corneal biomechanical metrics (CH & CRF) are associated with arterial stiffness – a well-established marker of future cardiovascular (CV) events and mortality. Methods: From an initial pool of 5065 participants from the community-based UK Biobank study, 4018 were rejected for missing data, leaving a cohort of 1047 individuals (male/female ratio: 0.496, mean age: 62 years, white ethnicity: 96.1%) (Table 1 ). Corneal biomechanical metrics (CH & CRF), were obtained using a Reichert Ocular Response Analyzer (ORA). Arterial compliance was quantified by aortic distensibility (AoD) derived by cardiovascular magnetic resonance (CMR) imaging. The relationship between corneal and vascular compliance parameters was assessed using both Spearman rank correlation coefficient analysis, and univariable and multivariable regression analyses adjusting for potential influential confounding variables – age, sex, ethnicity, height, weight, systolic blood pressure (SBP), diastolic blood pressure (DBP), smoking status, regular alcohol intake, diabetes status and dyslipidaemia. Results: A significant weakly positive correlation was observed between CH and AoD at both the ascending aorta (AA) and proximal descending aorta (PDA) (AA: Rho = 0.08, p = 0.01; PDA: Rho = 0.11, p <0.01), however no significant correlation was observed between CRF and AoD. In univariable analysis, only CH produced significant changes in AoD at both the AA and PDA (AA: ß = +3.0% per 10% increase in CH, 95% CI = 0.6 to 5.5, p = 0.02; PDA: ß = +2.6% per 10% increase in CH, 95% CI = 0.8 to 4.4, p = 0.004) (Figure 1 ). There was no significant linear relationship between CH or CRF and AoD in multivariable regression analysis, at both the AA and PDA (CH at AA: ß = +0.8% per 10% increase in CH, 95% CI = -0.9 to 2.6, p = 0.37; CH at PDA: ß = +0.8% per 10% increase in CH, 95% CI = -0.3 to 2.0, p = 0.16; CRF at AA: ß = +1.3% per 10% increase in CH, 95% CI = -0.4 to 3.0, p = 0.13; CRF at PDA: ß = +0.9% per 10% increase in CH, 95% CI = -0.3 to 2.0, p = 0.13). Conclusion: In this community-based cohort, we observed a weakly significant general correlation between CH and AoD. After adjustment for potential confounding factors, we then observed no significant relationship between corneal and aortic biomechanical indices, suggesting that in a general population, biomechanical corneal indices are not independently associated with parameters of central arterial compliance. Conflict of Interest: None